The encyclopedia of Civil War medicine - Schroeder-Lein, Glenna R., 1951- (M.E. Sharpe, Inc., 2008)
Clearly organized, authoritative, and readable, this first-of-its-kind encyclopedia offers general readers and scholars alike detailed coverage of the amazing saga of Civil War medicine on both sides of the conflict.